STATUS OF DIRECTION AND COMPETITION IN SPORTS SPORTS SPECIALTY - I.Fozilov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
Among the factors determining the level of development in a particular sport, great importance is attached to the selection, which is an integral part of many years of sports training and one of the important tasks.